Anthelmintic Activity of Aqueous Extract of Pongamia pinnata Linn. - ANBU JEBA SUNILSON*, J.; JAYARAJ, P.; VARATHARAJAN, R.; ANANDARAJAGOPAL, K.; REJITHA, G.; SURAJ, R. (Asian Journal of Chemistry, 2009)
Anthelmintic activity of the various doses of aqueous extract of Pongamia pinnata Linn leaves was evaluated on earthworms (Pheretima posthuma) and the results were compared with standard drug, albendazole (10 mg/mL). It was found that there was no final recovery in the case of worms treated with aqueous extract of Pongamia pinnata. Aqueous extract of Pongamia pinnata Linn also exhibited dose dependant inhibition of spontaneous motility (paralysis) and death of earthworms. Aqueous extract of Pongamia pinnata Linn showed highly significant (p < 0.001) anthelmintic activity at the concentration of 50 mg/mL. The results showed that the aqueous extract of Pongamia pinnata Linn possesses wormicidal activity and be useful as an anthelmintic.